Giving Peru a productivity boost: towards a system of continuous education and training - Lavado, Pablo (2015)
In spite of impressive rates of economic growth, the quality of the labor force’s human capital is considered a major challenge for sustaining medium term economic growth in Peru. This note reviews the skills of the Peruvian labor force, and the status of the continuous education and training system. Based on such an assessment and on learnings from international best practices, it proposes a system of continuous education and training that draws from international best practices, but that addresses local capacity and institutional issues.